ADSORPSI ION LOGAM KADMIUM (II) MENGGUNAKAN MAGNETIT (Fe3O4)-ARANG AKTIF KULIT BUAH TATAP (Artocarpus odoratissimus) - Fatmawati, Ririn Anggraeni; Koesnarpadi, Soerja; Wirawan, Teguh (Jurusan Kimia FMIPA UNMUL, 2024)
Adsorption of cadmium (II) metal ions has been carried out using magnetite adsorbent (Fe3O4) and Fe3O4-activated charcoal composite of tarap fruit peel (Fe3O4-AA). The Fe3O4 adsorbent was made using the coprecipitation method from FeSO4.7H2O and FeCl3.6H2O with a mole ratio of 1:1. Composite adsorbent Fe3O4-activated charcoal from tarap fruit peel from Fe3O4 combined with activated charcoal from tarap fruit peel. The separation process uses the help of an external magnet, and the cadmium concentration is analyzed using an Atomic Absorption Spectrophotometer (SSA). on the adsorbent. The results of characterization using FT-IR on Fe3O4 show the presence of Fe-O groups and on Fe3O4-AA it shows the presence of Fe-O and -OH groups and there are C-O groups from activated charcoal. In XRD analysis, diffraction peaks were obtained which were not much different from standard Fe3O4Fe3O4 with a smooth and sharp crystal structure. Furthermore, in the VSM analysis, results were obtained in the form of magnetization curves which showed that Fe3O4 and Fe3O4-AA were superparamagnetic. The optimum conditions for the magnetite (Fe3O4) adsorbent at pH 6 with a contact time of 60 minutes and an adsorption capacity of 23.3664 mg/g, while the optimum conditions for the composite adsorbent Fe3O4-AA at pH 5 with a contact time of 45 minutes and a maximum adsorption capacity of 26.4550 mg/g. The absorption percentage of the Fe3O4 adsorbent was 95.042% and the Fe3O4-AA adsorbent was 95.092%.